Representing Multiculturalism in Encanto Movie - Setyo Rini, Gitarisza Novinka; E. Ngestirosa Endang Woro Kasih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Multiculturalism is the focus of discussion in the study of Encanto's film which is linked to Colombian culture and society in the United States. Using Hall's theory of representation, this study aims to explore the extent to which multiculturalism is found in Encanto's films, especially in Colombian society. This study uses a descriptive qualitative method and applied data from pictures, dialogues and narration in the movie. There are two main things that are highlighted, namely first, multiculturalism by underlining the expressive value in Colombian culture. The second issue is showing respect and willingness on diversity. The results of the study found that Colombian people show multiculturalism in their own culture related to the past history and various cultural backgrounds that accompany the existence of Colombian society today. The film Encanto is a representation of multiculturalism today.